Ideas, Interests and Institutions in Brazilian Rural Territorial Development Policy: A Study of Território Meio Oeste Contestado - Tecchio, Andréia; Grisa, Catia; Oliveira, Luiza Zitzke; Cazella, Ademir Antonio (Íconos)
The territory ‘Meio Oeste Contestado’, located in Santa Catarina, Brazil, was created in 2003, after the implementation of the rural territorial development policy of the government of Luiz Inácio Lula da Silva (2003-2010). This article analyzes how social and political relations were established and administered in the territory; how the disputes between different actors and interests were dealt with; the ideas and interpretations that were at stake; and what territorial rules and regulations were established for the negotiation and conciliation between the different social actors. In general, we observe that the ideas that the territorial actors have about public policies for rural territorial development differ from those of the federal government. The main interest of the different actors in the territority is to raise more financial resources for the local organizations and municipalities in the territory due to the fragile nature of the different territorial institutions.